Non-isothermal crystallization behavior of PP/EVA/basalt/carbon fiber composites. Issue 4 (4th November 2020) - Ying, Xia; Fengfeng, Zhang; Huimin, Zhou; Qian, Yang; Xiaojian, Lin; Guozhong, Li
Abstract: The surface treatment of basalt and carbon fiber was carried out by sulfuric acid etching and coupling. Combined fiber was prepared by melt mixing. Polarizing optical microscope (POM) and differential scanning calorimetry (DSC) were employed to investigate the effect of combined fiber on crystallization behavior. To be specific, POM indicated that the addition of combined fiber reduced the crystal size. DSC observations illustrated that the combined fiber accelerated the crystallization rate and increased the crystallization temperature from 112-122 °C to 122-133 °C. It means that combined fiber can make the composites crystallize rapidly at high temperature in production. Modified Avrami models were used to evaluate the influence of combined fiber on the non-isothermal crystallization kinetics of PP. The presence of combined fiber reduced the Avrami exponent (n) from 2.16-3.13 to 1.54-2.49. The results showed that the combined fiber acted as heterogeneous nucleation agent, which changed crystal nucleation mechanism and growth mode. Graphical Abstract: